Nitrogen and phosphorus transfers in a crop-livestock system in West Africa - Powell, J.M.; Mohamed-Saleem, M.A. (Elsevier, 1987)
Investigates Nitrogen and Phosphorus transfers in a crop - livestock system in the subhumid zone of Nigeria. Estimates N and P removed from cropland during crop residue grazing and returned to the land through manure, and the contribution crop residues make to cattle diet during the dry season.